(untitled) (Polis (Santiago), 2018)
Starting from a reflection about the different modern conceptions of human rights, the author exposes the differences between possessive individualism and communicative personalism. The present ruling neoliberalism would be the result of the exacerbación of this first conception, that pleads for certain individual rights (specially private property) over other collective rights recognized since old Greece. The Globalization takes the form of an individualistic appropriation of the Law, that imposes a depredatory and abusive logic over the guarantees that had been achieved by communities and popular movements since XIX century.